2017
DOI: 10.1017/s0963548317000244
|View full text |Cite
|
Sign up to set email alerts
|

A Stronger Bound for the Strong Chromatic Index

Abstract: We prove χ s (G) 1.93Δ(G) 2 for graphs of sufficiently large maximum degree where χ s (G) is the strong chromatic index of G. This improves an old bound of Molloy and Reed. As a by-product, we present a Talagrand-type inequality where we are allowed to exclude unlikely bad outcomes that would otherwise render the inequality unusable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 26 publications
2
59
0
Order By: Relevance
“…Erdős and Nešetřil (see ) conjectured χ-2.3pts(G)54normalΔ2, and much of the research on the strong chromatic index is motivated by this conjecture. Building on earlier work of Molloy and Reed and Bruhn and Joos , Bonamy et al showed χ-2.3pts(G)1.835normalΔ2 provided that normalΔ is sufficiently large. For further results on the strong chromatic index, we refer to .…”
Section: Introductionmentioning
confidence: 92%
“…Erdős and Nešetřil (see ) conjectured χ-2.3pts(G)54normalΔ2, and much of the research on the strong chromatic index is motivated by this conjecture. Building on earlier work of Molloy and Reed and Bruhn and Joos , Bonamy et al showed χ-2.3pts(G)1.835normalΔ2 provided that normalΔ is sufficiently large. For further results on the strong chromatic index, we refer to .…”
Section: Introductionmentioning
confidence: 92%
“…Next we need a concentration inequality of Bruhn and Joos [4], derived from Talagrand's inequality [20]. To that end, we introduce the following definition.…”
Section: Probabilistic Toolsmentioning
confidence: 99%
“…Bruhn and Joos [9] proved that v 0 s ðGÞ 1:93D 2 ðGÞ, for graphs of sufficiently large maximum degree. This improves an old bound of v 0 s ðGÞ 1:998D 2 ðGÞ proved by Molloy and Reed [32].…”
Section: Introductionmentioning
confidence: 99%